Albania : 2018 First Post-Program Monitoring Discussions-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2018)
This paper discusses First Post-Program Monitoring Discussions in 2018 with Albania. The Albanian economy has continued to strengthen, with real GDP growth at 3.8 percent (year-over-year) during 2017, reflecting strong domestic demand driven by a revival in construction, recovery in the labor market and household credit, and large energy-related foreign direct investment projects. Although the public-debt-to-GDP ratio declined, the pace of fiscal consolidation has slowed post-program, with arrears accumulating. Despite the favorable environment and positive short-term outlook, risks and vulnerabilities remain, emanating from high public debt, non-performing loans in the financial sector, and weaknesses in public institutions and the judicial system.